PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY RATIO, DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA (STUDI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019- 2022) - Florencia Irena Ie; Jesslyn; Mahmuddin Syah Lubis; Yusneni Afrita Nasution (Mount Hope Economic Global Journal, 2024)
The purpose of this study is to determine the effect of Current Ratio, Debt to Equity Ratio, Return on Equity Ratio, and Net Profit Margin on Stock Prices of Food and Beverage Manufacturing Companies listed partially and simultaneously on the Indonesia Stock Exchange between 2019 and 2021. When evaluating a company, investors focus on one aspect. Financial ratio studies show good financial results. In general, a company's stock price increases in response to increased demand for its shares, which arises from increased profit margins. The population of this study consisted of 26 food and beverage manufacturing companies listed on the IDX in 2019 to 2022, while the sample was 68 analysis units. The multiple linear regression analysis approach was applied in the research process. The research findings show that stock prices are each influenced by the current ratio, debt to equity ratio, return on equity ratio, and net profit margin. Stock prices on the Indonesia Stock Exchange (IDX) are influenced by the following ratios: current ratio, debt to equity ratio, return on equity ratio, and net profit margin (Study of Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the IDX 2019–2022).